Value chain finance : developing a "value chain finance" business model of collaborative cash-to-cash optimization - Toukam, Edouard (Great Britain CreateSpace, 2012)
The book is a profound research and analysis in the area of supply chain finance within the context of DBA. It examines the cash-to-cash or cash conversion cycle as a tool for assessing how well companies manage capital and therefore can be used to improve firm's liquidity.
Includes bibliographical references p. 53-63
usc 25/10/17
Loans
Keywords: Value chain finance; Small businesses; Enterprise development